Newly synthesized lipid-porphyrin conjugates: evaluation of their self-assembling properties, their miscibility with phospholipids and their photodynamic activity in vitro - Massiot, Julien; Tanaka, Motomu (Chemistry - a European journal, 2018)
Lipid-porphyrin conjugates are considered nowadays as promising building blocks for the conception of supramolecular structures with multifunctional properties, required for efficient cancer therapy by photodynamic therapy (PDT). The synthesis of two new lipid-porphyrin conjugates coupling pheophorbide-a (Pheo-a), a photosensitizer derived from chlorophyll-a, to either chemically modified lyso-phosphatidylcholine (PhLPC) or egg lyso-sphingomyelin (PhLSM) is reported. The impact of the lipid backbone of these conjugates on their self-assembling properties, as well as on their physicochemical properties, including interfacial behavior at the air/buffer interface, fluorescence and absorption properties, thermotropic behavior, and incorporation rate in the membrane of liposomes were studied. Finally, their photodynamic activity was evaluated on esophageal squamous cell carcinoma (ESCC) and normal esophageal squamous epithelium cell lines. The liposome-like vesicles resulting from self-assembly of the pure conjugates were unstable and turned into aggregates with undefined structure within few days. However, both lipid-porphyrin conjugates could be efficiently incorporated in lipid vesicles, with higher loading rates than unconjugated Pheo-a. Interestingly, phototoxicity tests of free and liposome-incorporated lipid-porphyrin conjugates demonstrated a better selectivity in vitro to esophageal squamous cell carcinoma relative to normal cells.